Analysis of the mediation and ‘conciliation’ system brought by the 2015 Civil Procedure Code in the light of the concept of conflicts as property - Nicolau, Rafael Machado Viviani (2018)
The present essay analyses, with a critical view, the institutes of mediation and conciliation in the 2015 Brazilian Civil Procedure Code, based on Nils Christie’s ideas in Conflicts as Property. Both positive and negative aspects of the New Code are brought to light, inserting the 2015 CPC into the context of the ADR Movement. The conclusion is Universities should pursue to adjust their teachings of Law to the real needs of the community, forming professionals who question and create knowledge, promoting the amicable conflict-solving culture (“Pacification Culture”), restorative Justice, and the inclusion of the lay community in the processes of conflict solving.O presente artigo analisa de maneira crítica os mecanismos de mediação e conciliação no Código de Processo de 2015 com base nas ideias de Nils Christie em Conflicts as Property. De forma geral, destacam-se alguns pontos positivos trazidos pelo Novo CPC, bem como outros negativos, e contextualiza-se o CPC de 2015 dentro do Movimento ADR. Conclui-se pela enorme responsabilidade das Universidades, que devem buscar um ensino jurídico adequado às reais necessidades da sociedade, formando profissionais questionadores e produtores de conhecimento, que promovam a cultura da pacificação, da restauração e da inclusão da sociedade leiga nos processos de resolução de conflitos